2012
DOI: 10.1007/s10165-012-0690-1
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasonography is a potent tool for the prediction of progressive joint destruction during clinical remission of rheumatoid arthritis

Abstract: PD-US detects synovitis causing joint destruction even when the patient is in clinical remission. Thus, remission visible on US is essential to reach "true remission" of RA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
34
0
8

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(43 citation statements)
references
References 41 publications
1
34
0
8
Order By: Relevance
“…Twenty-two patients maintained remission after 2 years of follow-up. Seven patients had evidence of radiographic progression, which was significantly associated with PD activity at baseline [56]. Other studies have shown similar trends [57,58].…”
Section: Ultrasoundmentioning
confidence: 68%
“…Twenty-two patients maintained remission after 2 years of follow-up. Seven patients had evidence of radiographic progression, which was significantly associated with PD activity at baseline [56]. Other studies have shown similar trends [57,58].…”
Section: Ultrasoundmentioning
confidence: 68%
“…À l'échelle du patient 1.1.1. Fréquence des synovites échographiques dans la PR en rémission Globalement, à l'échelle du patient, de nombreuses études transversales [12][13][14][15][16][17][18][19][20][21] et longitudinales [22][23][24][25][26][27][28][29] ayant inclus des sujets en rémission clinique montrent que 33,3 à 100 % d'entre eux présentent au moins une hypertrophie synoviale sur une articulation détectée en mode B et 14,9 à 93,3 % ont au moins une synovite avec hyperhémie Doppler (Tableaux 1 et 2). La diversité des populations étudiées, la définition de la rémission clinique et sa durée, le nombre variable d'articulations étudiées en échographie (de 6 à 44 articulations) expliquent ces écarts importants.…”
Section: Persistance De Synovites éChographique : Comparaison Aux Autunclassified
“…À l'échelle du patient. Trois études longitudinales [23,25,27] se sont intéressées au risque de progression radiographique à l'échelle du patient (Tableau 4). Elles diffèrent par la durée d'évolution des PR, la durée de suivi, les critères de rémission, les scores radiographiques et la définition de la progression radiographique retenus, le nombre d'articulations évaluées.…”
Section: 22unclassified
See 2 more Smart Citations